Comparison of preemptive ibuprofen, acetaminophen, and placebo administration in reducing peri‐ and postoperative pain in primary tooth extraction: A randomized clinical trial - Nabih Raslan; Toufic Zouzou (Wiley, 2021)
Abstract Background The management of pain resulting from anesthesia injection, tooth extraction and in the period after extraction is of great importance in pediatric dentistry. Objective The aim of this study was to compare the efficacy of the preemptive administration of ibuprofen or acetaminophen with placebo in reducing the pain during injection, extraction and postoperatively in children undergoing primary tooth extraction. Material and methods A randomized, placebo‐controlled, triple‐blinded clinical trial of cooperative children who needed primary molar extraction by local anesthesia. Sixty‐six children aged between 6 and 8 years were randomly assigned to one of three groups: (a) Acetaminophen syrup (320 mg/10 ml); (b) placebo solution; and (c) ibuprofen syrup (200 mg/10 ml). Each of the three solutions was given 30 min before administration of the local anesthetic agent. The Pain level was assessed using the Wong-Baker faces® pain rating scale after injection, extraction, and postoperatively. The Kruskal-Wallis and Mann-Whitney U test were used to evaluate the pain scores between groups at confidence level of 95%. Results The use of preemptive analgesics showed lower pain scores compared to placebo. Additionally, only ibuprofen significantly reduced pain scores compared to placebo at the points immediately after injection (p = 0.001), immediately after extraction (p = 0.0001) and 5 h after extraction (p = 0.002). Conclusion Preemptive usage of ibuprofen reduces injection pain and relieves both extraction and postoperative pain in children undergoing primary tooth extraction. What this paper or case report adds It adds the knowledge regarding pain relief of injection and extraction in children. Preemptive analgesic medications have a beneficial effect on alleviating postoperative pain following tooth extraction in children. Ibuprofen is an effective analgesic for postoperative pain relief in children undergoing primary tooth extraction. Why this paper or case report is important to pediatric dentists Pediatric dentists may consider preemptive ibuprofen in children before injection and extractions. Identifies that Ibuprofen is an effective method of reducing postoperative pain.